CONSUMERISM IN THE CONTEXT OF SUFISM EDUCATION - Putri, Yulita; Nurhuda, Abid (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Sufism is one of the scientific studies that many scholars admire in the current era of modernism. One that entered that era was consumerism which was identified with the heart of capitalism. Therefore the purpose of this study is to describe consumerism in the context of Sufism education. The method used is literature study, then the relevant data is collected and then the contents are analyzed and finally concluded. The results of the study show that consumerism in the context of Sufism education needs to be controlled because it is an exaggerated behavior, only oriented towards worldly satisfaction and fosters arrogance so there should be an effort to restrain desire by fasting and always feeling enough.